Hydroxylamine Contributes More to Abiotic N2O Production in Soils Than Nitrite - Liu, Shurong; Schloter, Michael; Hu, Ronggui; Vereecken, Harry; Brüggemann, Nicolas (Frontiers in Environmental Science, 2019)
Nitrite (NO2-) and hydroxylamine (NH2OH) are important intermediates of the nitrogen (N) cycle in soils. They play a crucial role in the loss of nitrous oxide (N2O) and nitric oxide (NO) from soil due to their high reactivity. In this study, we collected soil samples from three ecosystems (grassland, arable land and forest with a riparian zone) and explored the contribution of NO2- and NH2OH to N2O formation in the different soils after exposure to oxic or anoxic pre-treatment. In addition, the importance of abiotic processes on the N2O formation from the two intermediates was studied by irradiating the soil samples with γ-irradiation. Our results demonstrate that NO2- addition induced the largest N2O production in the grassland soil, followed by the forest and arable soils. Only 9–39% of the produced N2O after NO2- addition came from abiotic processes. NH2OH addition increased N2O emissions the most from the arable soil, followed by the grassland and forest soils. The conversion of NH2OH to N2O was mostly (73–93%) abiotic. Anoxic pre-treatment decreased N2O production from NH2OH remarkably, especially for the grassland soil, while it increased N2O production from NO2- for most of the soils. Correlation analysis showed that NO2- effects on N2O production were strongly correlated with NH4+ content in soils with anoxic pre-treatment, while NH2OH effects on N2O production were strongly correlated to soil Mn and C content in soils with oxic pre-treatment. Our results indicate that NH2OH plays an important role for abiotic N2O formation in soils with low C and high Mn content, while the effect of NO2- was important mainly during biotic N2O production. Anoxic periods prior to N addition may increase the contribution of NO2-, but reduce the contribution of NH2OH, to soil N2O formation.